SWIMMING and ITS DIMENSION CITIZEN a study of case in Cariacica Espirito Santo (Fiep Bulletin - online, 2015)
This article searchs to describe as if it can develop the citizenship through a psicomotor sport genuinamente adapted the sociomotricidade. The problem searchs to tell on the a lacks of the agreement of the citizenship concept, as it is acquired and the factors that can influence in general in the life and the society. With the educational sport being worked of correct form, inside of its principles the one that was servant, can be arrived at a relation with the citizenship learning what the law says and what with the sport the person learns. One becomes necessary to know our rights and duties, and also to act in the society with significant changes to improve the quality of life of the being of the being of the man with the implantation of sociomotoras activities. The sport has that to be understood as a right and practising the swimming of this form people become Human beings, learn themselves to be solidary, to respect the rules, to be cooperative, to work in group True a Human being at last.
Keywords: Swimming; citizenship; education